Rendahnya Literasi Remaja di Indonesia: Masalah dan Solusi - Rahmadanita, Annisa (Universitas Sebelas Maret Library, 2022)
The ease of access to social media owned by teenagers is considered to be able to make teenagers spend most of their time without clear goals. On the other hand, youth are part of a digital community that participates in the progress of their country. This phenomenon is the background of this study. The goal of this research was to find a solution to the youth's low literacy rate. The method of this study is a literature review. The research findings show that in order to realize literate youth, collaboration and commitment from three important elements are needed, namely family, government, and society. The conclusion from this study is that the solution to low adolescent literacy is to realize literate youth through efforts to build high motivation for individual youth to think, read, and write, which can be built through the role of family elements. The next element is that the government, as a regulator, can play a role in issuing policies that support Indonesian families to improve literacy. The author considers that the various benefits received by adolescents through social media should be accompanied by restrictions on access to their use. Limiting access to social media can be outlined in a clear government policy. The next element is the community, which can play a role in educating and raising awareness regarding climate change and strengthening literacy for young people in Indonesia through a healthy internet campaign for young people. Communities can also build youth literacy communities and obtain assistance from the government, both at the central government and local government levels.